Sacred medicine : a doctor's quest to unravel the mysteries of healing - Rankin, Lissa, 1969- (Sounds True, 2022)
"From New York Times bestselling author Dr. Lissa Rankin comes a groundbreaking guide offering hope for healing when all else has failed"--